Acute Spinal Cord Contusion in a Patient with Multiple Upper Cervical Fractures, Parkinson's Disease, and Torticollis: Surgical Management. (11th September 2020) - Merrill, Sarah; Kalani, Maziyar A.; Patel, Naresh P.; Lyons, Mark K.; Neal, Matthew T.
Abstract : Case Report . Spine surgery in patients with Parkinson's disease (PD) involves increased risk. We describe a case of cervical myelopathy in a patient with PD, multiple fractures involving the atlas and axis vertebrae, and spasmodic torticollis. The patient was successfully treated with an upper cervical decompression and occipital-cervical (OC) fusion surgery. Strategies for torticollis reduction and successful surgical outcome are discussed. Risks and benefits must be carefully weighed when considering occipital cervical fusion in PD patients. Conclusion . Intraoperative manual reduction of laterocollis is possible after general endotracheal anesthesia, and continuous neuromonitoring is established. Use of optimizing strategies such as perioperative botulinum injections and intraoperative O-arm navigation should be considered.